اسلامی تناظر میں تدبیرِ منزل کے عناصر ترکیبی اور افرادِ خانہ کے حقوق و فرائض: ایک تحقیقی جائزہ: Compositional Elements of Planning in the Islamic Context and the Rights and Duties of Family Members: A Research Review (Khairulummah, 2022)
AbstractIslam is a natural religion and a complete code of life. Just as it contains clear and bright teachings for guidance and happiness in other areas of life. Similarly, it contains basic beliefs, rituals, and family, social, economic, educational and judicial system laws.Planning is the basic unit of society. If someone wants to build a strong building, then he will install the brick in a strong and correct place. Similarly, the positive role of women in the society cannot be ignored in order to establish the floor on a correct and strong foundation.There are clear orders for the association of women in Surah Talaq, Surah An-Nisaa, etc. of the Holy Quran. Similarly, their rights and duties have also been described in detail in the blessed hadiths. The foundation of Tadbir Manzil is the husband and wife together. Now there are clear Islamic orders to run this family in a better way, but the role of women is important in it.In this article, the elements of Tadbir Manzil have been synthesized and the rights of family members have been examined in the Islamic context.
Keywords: Islam, Tadbir Manzil, Holy Quran, judicial system laws, family members